Holocene climate change and prehistoric settlement in the lower Danube valley. (18th August 2015) - Bonsall, C.; Macklin, M.G.; Boroneanţ, A.; Pickard, C.; Bartosiewicz, L.; Cook, G.T.; Higham, T.F.G.
Abstract: An analysis of the summed probability distributions of 293 radiocarbon dates from Late Glacial to mid-Holocene sites in the Danubian Iron Gates highlights the existence of well-marked 14 C discontinuities at c. 9.5–9.0 ka, 8.65–8.0 ka and after 7.8 ka cal BP. These coincide with climate anomalies recorded in Greenland ice cores and palaeoclimate archives from the Danube catchment. Four possible explanations are considered: dwindling fish resources, changes in the social environment, flood-induced settlement relocations, and taphonomic effects. On present evidence, the last two factors are thought to be the most likely cause of the discontinuities observed in the Iron Gates Mesolithic–Early Neolithic radiocarbon record.